New and poorly known species of family Candonidae (Crustacea, Ostracoda, Podocopida) from Lake Baikal - Alekseeva, Tatyana M.; Krivorotkin, Roman S.; Timoshkin, Oleg A. (Zootaxa, 2025)
The ostracod fauna of Lake Baikal is characterized by a high diversity of species, most of which require revision, since their structure is insufficiently studied. In this work, we present illustrated redescriptions of morphological traits of five poorly known endemic Baikalian species of the genus Pseudocandona Kaufmann, 1900: Pseudocandona alta Bronstein, 1947, Pseudocandona werestschagini (Bronstein, 1930) Bronstein 1947, Pseudocandona renalis Mazepova, 1982, Pseudocandona glauci Mazepova, 1990 and Pseudocandona olchonica Mazepova, 1990. The redescriptions were prepared on the basis of a type collection of Baikal ostracods sampled by an outstanding researcher of Baikal, Prof. G.F. Mazepova. Additionally, we describe six new species: Pseudocandona grygieri Alekseeva & Krivorotkin sp. nov., Pseudocandona geminata Alekseeva & Krivorotkin sp. nov., Candona concava Alekseeva & Krivorotkin sp. nov., Candona korolevae Alekseeva & Krivorotkin sp. nov., Candona lanata Alekseeva & Krivorotkin sp. nov. and Candona perforata Alekseeva & Krivorotkin sp. nov. All species were carefully examined by light and scanning electron microscopy. The species under study are endemics of Lake Baikal and are extremely morphologically diverse.